Socio-demograpfflc and clinical Characteristics of neonates born before 34 Weeks of gestation: a case control study - Mettananda, D.S.G.; Rajindrajith, S.; Adhihetty, D.; Goonewardena, A.R.; Adikari, A.M.C.; Pannala, W.S.; Devanarayana, N.M.; Mettananda, K.C.D. (The Sri Lanka College of Paediatricians, 2008)
BACKGROUND: Management of neonates born before 34 weeks of gestation demands special resources and'' facilities which are limited in Sri Lanka. Identification of pregnancies at risk of preterm deliveries will enhance the optimal use of these neonatal facilities by appropriate and timely referrals. Objective: To compare th'e socio-demographic and clinical characteristics of neonates born before 34 weeks of gestation with those of term neonates. DESIGN, SETTING AND METHOD: A case-control study was conducted at the university obstetric unit of the North Colombo Teaching Hospital in the year 2006. All neonates born before 34-weeks of gestation were recruited as cases and a randomly selected group of term neonates was recruited as controls into the study after obtaining maternal consent. Data was collected by interviewing mothers and using patient records. RESULTS: Seventy cases and an equal number of controls were recruited. Forty (57%) cases and 30 (43%) controls were males. Mean birth weight was 1.44 (SD=0.46) kg for cases and 2.94 (SD=0.35) kg for controls. Previous history of preterm deliveries was found in 06 (8.6%) cases and. 01 (1.4%) control. Multiple pregnancy [OR=14.3,95% 01=1.8-113] and monthly family income less than Rs.lO,000/= [OR=2.6, 95% Cr^Ll-5.8] carried a significantly higher risk of_deliveries before 34 weeks. Increased risk was also detected in subjects with obstetric [OR=4.2, 95% CI=2.0-8.8)] and fetal [OR=11.0, 95% CI=3.6-33.6] complications. Maternal blood group, maternal education level and social class assessed by father's occupation did not have any association with deliveries before 34 weeks. Mean 1-minute APGAR was significantly lower in neonates born before 34 weeks [7.2 (SD=2.9)] than controls [9.7 (SD=0.5)], (pO.OOl) and the same was true for the score at 5 minutes. CONCLUSIONS: Multiple pregnancies, presence of maternal or fetal complications and low family income were associated with increased risk of deliveries before 34 weeks of gestation. Apgar scores at 1 and 5 minute were lower in neonates born before 34 weeks of gestation.
OP5 - Abstract of the Annual Scientific Congress of the Sri Lanka College of Paediatricians 2008
Keywords: neonates